Do like Kyla - Johnson, Angela, 1961-; Ransome, James (New York : Orchard Books, 1990)
A little girl imitates her big sister Kyla all day, until in the evening Kyla imitates her.
"A Richard Jackson book"--P. [1]
Keywords: Sisters -- Fiction; African Americans -- Fiction